The Eye of the Storm: COVID-19 Vaccination and the Eye - Ng, Xin Le; Betzler, Bjorn Kaijun; Ng, Sean; Chee, Soon Phaik; Rajamani, Lakshminarayanan; Singhal, Amit; Rousselot, Andres; Pavesio, Carlos E.; Gupta, Vishali; de Smet, Marc D.; Agrawal, Rupesh (Ophthalmology and therapy, 2022)
The COVID-19 pandemic has galvanized the global response towards the development of new vaccines based on novel technologies at an unprecedented pace. Since the widespread implementation of vaccination campaigns, case reports on vaccines' systemic side effects, including ocular manifestations, have emerged. Since administered vaccines are generally not able to cause the disease in the recipient, or induce an immune response against the pathogen, we hypothesize that the development of ocular phenomena post-COVID-19 vaccination may occur via an immune response elicited by the vaccine. Of many, the most common ocular adverse events include facial nerve palsy, central venous sinus thrombosis and acute anterior uveitis. These COVID-19 vaccine-induced ocular (CVIO) adverse events could resemble the ocular findings in some of the COVID-19 patients. This review will provide a comprehensive overview of published ocular side effects potentially associated with COVID-19 vaccination and serve as a springboard for further research into CVIO adverse events.